Die Höhe und Verwendung von Löhnen für Kinderarbeit, 1853-1938 - Manuel Schramm (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– Although child labour itself is well researched, no reliable data yet exists on the level of wages for children, which are usually described as fluctuating. Here, using Saxony as an example, an attempt is made to trace the development of wages for children over almost a century. It shows that wages did fluctuate, but only within a limited corridor. Surprisingly, wage levels remained largely the same, except for the inflation years. Furthermore, the use of the income is examined. Most of it went into the general family budget, but for some working children (and even more so for youths), work opened up the possibility of spending money for their own purposes.
Keywords: N33; N34; 330; Child labour; labour history; wages; standard of living